Ecofeminist Practices in the Novel Batu Berkaki by Chandra Bientang: An Analysis of Vandana Shiva - Lidiya Mushiyam Nurhidayah; Abdul Kholiq (Raja Zulkarnain Education Foundation, 2026)
Grounded in Vandana Shiva’s ecofeminism theory (Staying Alive), this study examines Chandra Bientang’s novel Batu Berkaki to uncover the close link between the oppression of women and ecological destruction rooted in the patriarchal-capitalist system. Utilizing a qualitative descriptive approach, this research focuses on the mechanisms of women’s marginalization and the vital role of f emale characters in defending the ecology and economy against the pressures of maldevelopment. The findings successfully identify 58 data points divided into two primary axes: oppression and resistance. Within the oppression axis, the study reveals that the environmental exploitation driven by the character Mugyono not only destroys the welfare of Ledok Awu’s residents but also marginalizes women on multiple levels. The tragic death of Mbok Im symbolizes the destruction of the feminine principle, while the social exclusion of Turkiyem and Ruminem serves as a form of symbolic violence meant to silence their voices. Conversely, within the resistance axis, these female characters consistently actualize Shiva’s feminine principle. They act as ecological guardians and pillars of the village’s subsistence economy; Mbok Im establishes a communal learning space, Turkiyem consistently nurtures the land and passes down traditional herbal knowledge, while Lasmi and Kundari smuggle seeds to prevent the village’s food sources from being entirely monopolized by corporations. This research is expected to contribute not only to Indonesian literary studies but also to environmental education practices.